Cost-effectiveness of expanding the target population of biennial screening for breast cancer from ages 50–69 to 45 and/or 74: A cohort modelling study in the Finnish setting - Siegfrids, Filip; Heinävaara, Sirpa; Sarkeala, Tytti; Niinikoski, Laura; Laine, Juha (Springer Science and Business Media LLC, 2025)
Background
Within Finland's breast cancer screening program, all women aged 50-69 are invited to biennial screening. Current European guidelines recommend screening in ages 45-49 and 70-74 conditional upon, inter alia, demonstrated context-specific cost-effectiveness. This study aims to determine the cost-effectiveness of expanding the target population of biennial screening to ages 45 and/or 74, compared to the current national breast cancer screening strategy, in the Finnish setting.
Methods
Screening strategies' costs and quality-adjusted life years (QALY), aggregated over a lifetime horizon for the population simulated through a decision-analytic model, allow for comparison through incremental cost-effectiveness ratios. The model, using a Markov cohort simulation approach, was adapted to the cancer stage classification system used by the Finnish Cancer Registry (FCR) and calibrated to observed metrics in the Finnish female population. The analysis was conducted from a limited societal perspective, using a discount rate of 3% for costs and outcomes. Sensitivity analyses were performed to assess decision uncertainty, using an implicit willingness-to-pay (WTP) threshold range of 25 000-50 000 per incremental QALY.
Results
Compared to the current national screening strategy, both strategies with a starting age of 45 were cost-effective at the WTP-threshold of 50 000 per incremental QALY. Biennial screening in ages 45-69 was also cost-effective at 25 000 per QALY and demonstrated the highest probability of cost-effectiveness of all screening strategies over the whole WTP-threshold range of 25 000-50 000 per QALY. Biennial screening in ages 50-74 was dominated by all strategies over the threshold range.
Conclusions
Expanding the national screening strategy target population age is likely to produce net health benefits to acceptable costs, insofar as women aged 45-49 are covered by the expansion. Only expanding the target population to age 74 is unlikely to be cost-effective, given a WTP-threshold range of 25 000-50 000 per incremental QALY.